Mental health challenges and substance use in student-athletes: prevalence and impact - Moore, Erin M.; Simmons, Maylasia A.; Threatt, Julianna (Frontiers in Sports and Active Living, 2025)
BackgroundMental health significantly impacts athletes’ daily functioning and performance. Some coping techniques, such as substance abuse, can lead to addictive behaviors detrimental to sport participation.PurposeThis study aimed to identify the prevalence of anxiety, depression, and substance use in varsity student-athletes, examine their associations, and determine if academic and athletic factors (e.g., competition level, current sport season) are linked to these issues.MethodsAn anonymous survey assessed mental health (anxiety and depression) and substance use in varsity athletes aged 18–25 participating in organized sports (high school, Junior College, NAIA, and NCAA Divisions I, II, III) and enrolled in academic classes. Four validated surveys were used: GAD-7 for anxiety, PHQ-9 for depression, AUDIT for alcohol use, and TAPS for substance use.ResultsSixty-two participants (19.87 ± 1.47 years; males: 30.6%, females: 67.7%) completed the study. Most participants (45.2%) were in-season, and 54.8% competed at the NCAA Division III level. Elevated levels of anxiety (64.5%), depression (62.9%), and substance use (alcohol: 59.7%; other substances: 49.18%) were reported. Only two participants reported illicit drug use (mushrooms). Significant associations were found between mental health issues, substance use, and athletic factors (competition level, sport season, academic year, sex).ConclusionThis study highlights the high prevalence of anxiety, depression, and substance use among student-athletes, particularly at the Division III level. These issues affect both academic and athletic performance. Clinicians should focus on early screening and be competent in recognizing and addressing mental health problems in student-athletes to make effective referrals.